Compression of remote sensing data using a lossless variable-length Delta encoding scheme - Gopalan, Kaushik; Kasparis, Takis (My University, 2007)
This paper considers the compression of remote sensing data with a lossless variable-length delta encoding scheme. Remote sensing data typically contains slow changing samples over large sections and hence is suitable for compression using delta encoding. We demonstrate that a simple delta encoding scheme operating on remote sensing data gives compression ratios that are comparable to those given by more complex compression packages.